Soziale Ungleichheit und Gesundheit: Stand und Perspektiven der sozialepidemiologischen Forschung in Deutschland = Social inequality and health : status and prospects of socio-epidemiological research in Germany - Lampert, Thomas; Schneider, Sven (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
Social differences in morbidity and mortality have always been a central topic in public health research. In recent years, there has been a growing research interest that has clearly resonated with the general public and the political arena as well. This article describes the development and establishment of social epidemiology in Germany and presents the current status of research. In addition, it describes different models for explaining health inequalities. On this basis, selected challenges and prospects of socio-epidemiological research are demonstrated. The reason why the analysis of social differences in morbidity and mortality will continue to be a key task of public health research in the national and international context in the future is also explained.